Create your own economy : the path to prosperity in a disordered world - Cowen, Tyler (New York : Dutton, 2009)
The coauthor of the'best economics blog in the universe' offers a guide to success in a radically new hyper-networked age. The way we think is changing more rapidly than it has in a very long time. Not since the Industrial Revolution has a man-made creation--in this case, the World Wide Web--so greatly influenced the way our minds work and our human potential. Cowen argues that we are breaking down cultural information into ever-smaller tidbits, ordering and reordering them in our minds (and our computers) to meet our own specific needs. He explains why the coming world of Web 3.0 is good for us; why social networking sites such as Facebook are so necessary; what's so great about'tweeting' and texting; how education will get better; and why politics, literature, and philosophy will become richer.--From publisher description.
The future of thinking differently -- Hidden creativity -- Why modern culture is like marriage, in all its glory -- IM, cell phones, and Facebook -- The Buddha as savior and the professor as shaman -- The new economy of stories -- Heroes -- Beauty isn't what you think -- Autistic politics -- The future of the universe.
Includes bibliographical references and index.
Keywords: Economics -- Psychological aspects; Creative thinking